Kinetics of the BrO + ClO reaction and implications for stratospheric ozone - Hills, Alan J.; Cicerone, Ralph J.; Calvert, Jack G.; Birks, John W. (1987)
The first direct measurements of the rate constant and product distribution of the BrO + ClO reaction as a function of temperature is reported. It is shown that this reaction could account for a large fraction of the springtime ozone depletion over Antarctica and provide a source of chlorine dioxide of sufficient magnitude to explain the recent measurements of this species in the Antarctic atmosphere, provided that the stratosphere contains a sufficient quantity of bromine.